In‐flight dynamics of volcanic ballistic projectiles. (30th July 2017) - Taddeucci, J.; Alatorre‐Ibargüengoitia, M. A.; Cruz‐Vázquez, O.; Del Bello, E.; Scarlato, P.; Ricci, T.
Abstract: Centimeter to meter‐sized volcanic ballistic projectiles from explosive eruptions jeopardize people and properties kilometers from the volcano, but they also provide information about the past eruptions. Traditionally, projectile trajectory is modeled using simplified ballistic theory, accounting for gravity and drag forces only and assuming simply shaped projectiles free moving through air. Recently, collisions between projectiles and interactions with plumes are starting to be considered. Besides theory, experimental studies and field mapping have so far dominated volcanic projectile research, with only limited observations. High‐speed, high‐definition imaging now offers a new spatial and temporal scale of observation that we use to illuminate projectile dynamics. In‐flight collisions commonly affect the size, shape, trajectory, and rotation of projectiles according to both projectile nature (ductile bomb versus brittle block) and the location and timing of collisions. These, in turn, are controlled by ejection pulses occurring at the vent. In‐flight tearing and fragmentation characterize large bombs, which often break on landing, both factors concurring to decrease the average grain size of the resulting deposits. Complex rotation and spinning are ubiquitous features of projectiles, and the related Magnus effect may deviate projectile trajectory by tens of degrees. A new relationship is derived, linking projectile velocity and size with the size of the resulting impact crater. Finally, apparent drag coefficient values, obtained for selected projectiles, mostly range from 1 to 7, higher than expected, reflecting complex projectile dynamics. These new perspectives will impact projectile hazard mitigation and the interpretation of projectile deposits from past eruptions, both on Earth and on other planets. Key Points: Volcanic Ballistic Projectiles (VBPs) in volcanic deposits, theory, and direct observations are reviewed High‐speed imaging and measurements of VBPs spinning, deforming, fragmenting, colliding, and impacting with the ground are provided In‐flight fragmentation, collisions, and spinning are important for VBPs dynamics, and apparent drag coefficient can be higher than expected Plain Language Summary: Explosive volcanic eruptions launch incandescent fragments, sometimes partially molten, to distances of up to several kilometers from the volcano. The largest fragments, from the size of an apple to that of a van, travel in air following the same laws that control the flight of artillery shells and, on landing, may cause the same harmful consequences. To protect people and properties from these volcanic projectiles, their occurrence in volcanic rocks is documented, and their motion is simulated by computer models. However, both field studies and computer models require validation, but in‐flight observation of the projectiles have been sparse, so far. We used state‐of‐the‐art high‐speed cameras, filming volcanic projectiles in slow motion to understand and measure the processes that control their flight dynamics. We found that the in‐flight deformation, rotation, and collision of the projectiles have a deep impact on their trajectory. We also measured the size of craters left by the projectiles on landing, and we derived specific parameters that are essential to model projectiles flight. We found that currently used models often do not account for all the in‐flight dynamics. Our findings will improve interpreting the motion of the projectiles and mitigating their hazard.